Chemoselective anti-Markovnikov hydroamination of alpha,beta-ethylenic compounds with amines using montmorillonite clay - Joseph, Trissa; Shanbhag, G. V.; Sawant, D. P.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A-Chemical, 2006)
The catalytic activity of montmorillonite clays as a catalyst for the hydroamination of alpha,beta-ethylenic compounds with amines was tested. Aniline and substituted amines reacted with alpha,beta-ethylenic compounds in the presence of catalytic amount of commercially available clay to afford exclusively anti-Markovnikov adduct in excellent yields. Aniline reacted with ethyl acrylate to yield only anti-Markovnikov adduct N-[2-(ethoxycarbonyl)ethyl] aniline (mono-addition product). No Markovnikov adduct (N-[1-(ethoxycarbonyl)ethyl]aniline and double addition product N,N-bis[2-(ethoxycarbonyl)ethyl]aniline were formed under selected reaction conditions. For a better exploitation of the catalytic activity in terms of increased activity and improved selectivity for the mono-addition product, the reaction parameters were optimized in terms of temperature, solvent, reactant mole ratio. Under optimized reaction conditions, montmorillonite clay K-10 showed a superior catalytic performance in the hydroamination of ethyl acrylate with aniline with a conversion of aniline to mono-addition product (almost 100% chemoselectivity) with a high rate constant 0.3414 min(-1) compared to the reported protocols. The dependence of conversion of aniline over different types of montmorillonite clays (K-10, K-20, K-30, Al-Pillared clay and untreated clay) has also been discussed. The activities of clay for the hydroamination of different aromatic and aliphatic amines have also been investigated. Under harsh reaction conditions (increased temperature and long reaction time) small amounts of di-addition products were observed. The kinetics data has been interpreted using the initial rate approach model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alpha; amines; anti-Markovnikov addition product; beta-ethylenic compounds; chemo-selective; hydroamination; K-10 montmorillonite clay